Qualidade da água subterrânea no município de Sinop sob diferentes cenários de uso e ocupação do solo - Garcia, Francisco Moacir Pinheiro (2015)
The research aimed to evaluate the quality of groundwater from Sinop city, Mato Grosso state, according to the use, land use and climate stations, for the presence of heavy metals: barium, copper, lead, iron, manganese and zinc, comparing them with limits established by CONAMA Resolution number 396 of 2008 and the Ordinance the Ministry of Health - MS, number 2914. Water samples were collected in two stages: in the dry season in September of 2013, and during the rainy season in March of 2014. The selection of the sampling sites was made based on the history of use and occupation of land by setting up five sectors and each sector 3 points. The sectors were defined as rural sector (1), industrial sector (2), central sector (3), southern residential sector (4) and north residential sector (5). The collection, transportation, preservation, preparation and analysis of was set in the Standard Methods for the Examination of Water and Wastewater (APHA, 1995). Metal concentrations were carried out by atomic absorption spectrometry apparatus. The experimental design was completely randomized (DIC), in a factorial design. 5 x 2 x 3, with 3 replications. When obtained significant differences, the data were submitted to the test averages Scott-Knott. To statistical analyzes, was used SISVAR software, version 5.1. The metals copper, manganese and zinc had the highest concentrations in the rainy season, the concentrations of lead and barium iron were higher in the dry season. Metals only surveyed lead and iron had concentrations above established by CONAMA Resolution number 396 and the Ordinance of the Ministry of Health - MS, number 2914. Regarding the use and occupation, the sectors: Rural and Southern Residential, require greater attention. It is believed that the above values of legislation are related anthropogenic emissions. Industry and trade do not contribute significantly to the contamination of groundwater from the city of Sinop. Therefore, to consume the groundwater has to perform Sinop water treatment by using activated charcoal or other adsorbent material to remove metals.